Design of a curry puff making machine - Ibrahim, Imran (2010)
Most of the processes of curry puff making in small scale industry are well known as handmade product where curry puffs are made by using human manpower completely. This certainly needs many human power and skilled operators to increase their production rate at high competitive level. In another side, experienced curry puff maker use the machine that imported from out of our country. This can be a burden for small scale industry player that want to start and continue their small business. This project is to design a curry puff making machine that will help industry player to start their business at low cost. To realize the model of the machine, a systematic approach called product design and development is implemented to ensure the proper design is completed. It is covers the concept development, concept scoring, selection and preliminary final design. Consequently a conceptual model of curry puff machine complete is created. For further step, this conceptual model will be designed in detail and model analysis will be performed to distinguish any design related issues. Curry puff making model is function semi-automatically where it is used to form and crimp the curry puff according to its mould shape. This machine consisting 8 units of plastic mould that capable of producing 8 pieces of curry puff in each operation and would be increased if required. It is use controlled mechanical power to ensure systematic operation is performed. At the same time, the material that used for machine structures are selected based on safety concern for food processing equipment.